Novel protein candidates for serodiagnosis of African animal trypanosomosis: Evaluation of the diagnostic potential of lysophospholipase and glycerol kinase from Trypanosoma brucei - Tounkara, Magamba; Boulangé, Alain; Thonnus, Magali; Bringaud, Frédéric; Bélem, Adrien Marie Gaston; Bengaly, Zakaria; Thévenon, Sophie; Berthier, David; Rivière, Loïc (PLOS Neglected Tropical Diseases, 2021)
African trypanosomosis, a parasitic disease caused by protozoan parasites transmitted by tsetse flies, affects both humans and animals in sub-Saharan Africa. While the human form (HAT) is now limited to foci, the animal form (AAT) is widespread and affects the majority of sub-Saharan African countries, and constitutes a real obstacle to the development of animal breeding. The control of AAT is hampered by a lack of standardized and easy-to used diagnosis tools. This study aimed to evaluate the diagnostic potential of TbLysoPLA and TbGK proteins from Trypanosoma brucei brucei for AAT serodiagnosis in indirect ELISA using experimental and field sera, individually, in combination, and associated with the BiP C-terminal domain (C25) from T. congolense. These novel proteins were characterized in silico, and their sequence analysis showed strong identities with their orthologs in other trypanosomes (more than 60% for TbLysoPLA and more than 82% for TbGK). TbLysoPLA displays a low homology with cattle (<35%) and Piroplasma (<15%). However, TbGK shares more than 58% with cattle and between 45–55% with Piroplasma. We could identify seven predicted epitopes on TbLysoPLA sequence and 14 potential epitopes on TbGK. Both proteins were recombinantly expressed in Escherichia coli. Their diagnostic potential was evaluated by ELISA with sera from cattle experimentally infected with T. congolense and with T.b. brucei, sera from cattle naturally infected with T. congolense, T. vivax and T.b. brucei. Both proteins used separately had poor diagnostic performance. However, used together with the BiP protein, they showed 60% of sensitivity and between 87–96% of specificity, comparable to reference ELISA tests. In conclusion, we showed that the performance of the protein combinations is much better than the proteins tested individually for the diagnosis of AAT.